Genomic medicine: evolving science, evolving ethics. (July 2012) - Soden, Sarah E; Farrow, Emily G; Saunders, Carol J; Lantos, John D
Genomic medicine is rapidly evolving. Next-generation sequencing is changing the diagnostic paradigm by allowing genetic testing to be carried out more quickly, less expensively and with much higher resolution; pushing the envelope on existing moral norms and legal regulations. Early experience with implementation of next-generation sequencing to diagnose rare genetic conditions in symptomatic children suggests ways that genomic medicine might come to be used and some of the ethical issues that arise, impacting test design, patient selection, consent, sequencing analysis and communication of results. The ethical issues that arise from use of new technologies cannot be satisfactorily analyzed until they are understood and they cannot be understood until the technologies are deployed in the real world.